Analisis Persediaan Beras Nasional dalam Memenuhi Kebutuhan Beras Nasional pada Perusahaan Umum Bulog - Wijayanti, Safitri; Candra, Sevenpri; Sarjono, Haryadi (Bina Nusantara University, 2011)
Research showed that during 1998 to 2006, the minimum inventory needs of national rice is less than the expected inventory needs of national rice. Inventory trend is almost decreasing because of the quantum transmission inventory is beyond over of inventory increasing internal nation to the inventory of national rice decreasing. Partially, internal inventory affects the positive income towards national rice inventory; rice import has no effect towards the inventory of national rice; rice transmission is affected towards national rice inventory. This thing shows that rice inventory controlling in Perum Bulog must pay attention to internal rice procurement circumstances. On the other hand, importing rice is only as complement and done if needed. The rice inventory has negative influence towards price in producer level. This shows that internal procurement procedure needs to be changed.